The Study Methods of Increase Efficiency Algorithms Pulse width Modulation in AC Electric Drives - Bogdan Y. Vasilev (Institute of Advanced Engineering and Science, 2016)
In the paper describes the AC electric drive, which consists of the induction motor and the semiconductor converter. Structure of the frequency converter, which includes a three-phase bridge inverter on based fully controlled transistors, is considered. The algorithm of pulse width modulation, which used in the majority of the electric drives, is discussed. The characteristics and shortcomings of the algorithm is shows. Algorithmically methods to improve the efficiency of the inverter – promodulation control signal. The efficiency of this method in different variations is given. The level electromagnetic compatibility inverter and efficiency various control algorithms are analyzed. The conclusions about feasibility of using the method promodulation.